THE EFFECT OF DEBT POLICY ON COMPANY VALUE IN THE PULP AND PAPER SUB SECTOR LISTED ON BEI - alfin akuba (Institut Teknologi Adhi Tama Surabaya, 2021)
This study aims to determine and analyze how much influence the Debt Policy (X) partially affects Firm Value (Y). This research is a quantitative study, using ratio analysis. The analysis method uses simple linear regression. The results showed that the Debt Policy (X)) partially did not have a significant effect on Firm Value (Y) in the Pulp and Paper sub-sector that went public on the Indonesia Stock Exchange of 0.449. Keywords: Debt Policy and Company Value